Enhancement and suppression of a euchromatic position effect at Notch in Drosophila melanogaster. - Welshons, W.J.; Welshons, H.J. (Genetics, 1986)
The recessive visible rough-eye mutant facet-strawberry, fa(swb), is caused by the deletion of 0.8 kb of base sequences from the 5' end of the Notch locus. Visible deficiencies adjacent to fa(swb) suppress this mutant effect of the Notch locus, and in the same region (between salivary bands 3C1 and 3C7), we have demonstrated the presence of at least one partial suppressor and one enhancer of the fa(swb) position effect at Notch.-The enhancer seems to be a small inversion approximately equal to the salivary-band doublet 3C2, 3, and the partial suppressor lies between the inversion in 3C2, 3 and the small deletion in fa(swb) immediately distal to 3C7. Neither the enhancer, e(fa(swb)), nor the partial suppressor, su(fa(swb)), can be detected except when linked in cis to fa(swb). The e(fa(swb)) and the su(fa(swb)), in unison, act antagonistically on the fa(swb) position effect.-The fa(swb) mutant is interpreted to be a nonvariegating position effect at the Notch locus resulting from a novel euchromatic-euchromatic association of base sequences caused by the small deletion.